Development of Interactive Multimedia Using Articulate Storyline 3 to Enhance Learning Outcomes in Creative Fabric Lessons at a Vocational High School - Shofi, Amalia; Wahyuningsih, Sri Endah; Anis, Samsudin (Jurnal Penelitian Pendidikan, 2025)
This study aimed to develop interactive multimedia based on Articulate Storyline 3 and to test its feasibility, practicality, and effectiveness in teaching Creative Fabric to students in the Fashion Design Expertise Program at SMK Negeri 1 Purwodadi. The research method employed was Research and Development (R&D) using the ADDIE development model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The experimental research design used was a Pretest-Posttest Control Group Design, involving 60 11th-grade students divided into an experimental and a control class. The results showed that the developed interactive multimedia had a very high feasibility level, with 92.27% approval from media experts and 87.69% approval from material experts. The practicality test conducted by 10 teachers yielded a score of 86.94%, which falls into the "Practical" category. In terms of effectiveness, student learning outcomes in the experimental class showed significant improvement, with an average pretest score of 72.00 and a posttest score of 91.73. In contrast, the control class showed a pretest score of 65.87 and a posttest score of 79.20. The average N-Gain score in the experimental class was 0.7204 (categorized as "very effective"), while the average score in the control class was 0.3459 (categorized as "fairly effective"). A T-test analysis of the N-Gain scores yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between student learning outcomes in the experimental and control classes. Thus, interactive multimedia based on Articulate Storyline 3 has proven to be feasible, practical, and effective in improving student learning outcomes in the Creative Fabric subject within vocational education.